Dampak Integrasi Perilaku TMT dan Kualitas Pengambilan Keputusan Terhadap Transformasi Digital, Keunggulan Bersaing yang Berkelanjutan dan Kinerja Perusahaan - Indra Danardono; Soebowo Musa (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Digital transformation is essential for businesses in the digital age, but many struggle due to cultural barriers. This study examines the impact of Top Management Team on firm performance in the context of digital transformation. Through a survey of 140 professionals in Indonesian firms, the study finds that digital transformation encourages the development of Top Management Team Behaviour integration and Decision-Making Quality, which in turn leads to improved Firm Performance. The study also highlights the mediation effect of digital transformation and Sustained Competitive Advantage on this relationship.